Political Corruption and its Relationship to Illegal Immigration "Libya as an Ideal" (مجلة جامعة سرت للعلوم الانسانية, 2022)
Corruption is considered one of the most dangerous pests that afflict society, as its negative impact diffuses into political, economic and social life and leads to the spread of many negative phenomena, where corruption takes many different forms and manifestations. Libya is among the countries in which many forms of corruption have spread, especially in recent years, as a result of several reasons, including ongoing political disputes and political division, the spread of weapons in the hands of groups outside the control of the state, and the accompanying security vacuum. This made Libya a suitable environment for some negative phenomena, such as illegal immigration and human trafficking. These phenomena have become constantly increasing in light of the state’s inability to control human smuggling lines.
Keywords: Corruption; Corruption in Libya; Illegal Immigration